2020
DOI: 10.1186/s12917-020-02299-2
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to overcome flow cytometry limitations in the analysis of cells from veterinary relevant species

Abstract: Background: Flow cytometry is a powerful tool for the multiparameter analysis of leukocyte subsets on the single cell level. Recent advances have greatly increased the number of fluorochrome-labeled antibodies in flow cytometry. In particular, an increase in available fluorochromes with distinct excitation and emission spectra combined with novel multicolor flow cytometers with several lasers have enhanced the generation of multidimensional expression data for leukocytes and other cell types. However, these ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Thus, proving that those irregular shapes can also be quantified and compared. Therefore, these methods stand as an example for a cost-effective way of analysis and can potentially eliminate the need for sophisticated instruments such as flow cytometry that are not only expensive but also require frequent calibrations when using cell types of irregular geometry (Hunka et al, 2020). Thus, the findings from this study show that ImageJ can be used to effectively monitor the cells for use in various applications.…”
Section: Image Analysis As An Alternative Tool For Cell Sortingmentioning
confidence: 85%
“…Thus, proving that those irregular shapes can also be quantified and compared. Therefore, these methods stand as an example for a cost-effective way of analysis and can potentially eliminate the need for sophisticated instruments such as flow cytometry that are not only expensive but also require frequent calibrations when using cell types of irregular geometry (Hunka et al, 2020). Thus, the findings from this study show that ImageJ can be used to effectively monitor the cells for use in various applications.…”
Section: Image Analysis As An Alternative Tool For Cell Sortingmentioning
confidence: 85%
“…Data analysis was performed using FlowJo V.10.4.1 software (Tree Star, Ashland, Oregon, USA). Online supplemental figure 1 shows the gating strategy from our previous publication77 and follows other published studies 82 83. In this study, we reported on four activation phenotypes (CD38+HLA-DR+, CD38+HLA-DR−, CD38-HLA-DR+, and CD38−HLA-DR−) and define these as previously described 42 77 80.…”
Section: Methodsmentioning
confidence: 94%
“…Although only a small proportion of γδT cells can express IgG receptors in their membranes (CD16/FcγR3A), they are functionally differentiated by CTL activity [ 74 ]. The staining protocol used in our study was based on fluorophores attached to the monovalent affinity-purified Fab fragments directed against the Fc portion of IgG primary antibodies [ 75 ]. Therefore, the staining method hinders CD16 interactions by occupying the Fc portion of the IgG molecule, even allowing for simultaneous CD16 identification in complex cytometry staining panels as described in the literature [ 76 ].…”
Section: Discussionmentioning
confidence: 99%